Knowledge and Attitudes of Women toward the Influenza Vaccination during Pregnancy in Amman, Jordan - Barham, Yasmeen (Jordan Medical Journal, 2023)
Objectives: The study aimed to assess the level of knowledge and attitudes of Jordanian women regarding influenza and its vaccine during pregnancy. Methods: A cross-sectional study was conducted on 384 Jordanian women who had had a full-term delivery during the last 12 months. Data were collected with an interviewer-administrated questionnaire at five governmental comprehensive healthcare centers in Amman governorate. Results: Most participants had moderate knowledge (78.1%) (average score of 6.08 ± 1.38 out of 10). Women were either positive (51.0%) or neutral (47.9%) towards the influenza vaccination during pregnancy (average score of 52.43 ± 6.29 out of 75). Further, the vaccination rate during the women’s latest pregnancy was 2.1%. A significant positive relationship was found between the knowledge and attitudes of participants (p=0.001). Conclusion: The vaccination rate was low among women during pregnancy. The study’s results suggest that a greater awareness of the flu vaccine would help build positive attitudes towards its uptake during pregnancy. In this sense, antenatal care healthcare providers, such as gynecologists and midwives, should communicate strong health education messages about the flu vaccine as a preventative measure against influenza complications during pregnancy.